Memanusiakan Manusia Melalui Pendidikan di Dalam Keluarga Menurut Pemikiran Driyarkara dan Ki Hajar Dewantara - Gaudensius Krisantus Sutanto (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2025)
Article written by the author focuses on explaining about Driyarka and Ki Hajar Dewantara’s ideas and taught about education in the family. Ki Hajar Dewantara, put forward the concept of the Three Centers of Education, which states that education occurs in the family, school and social community, with the family as the first and main educational environment. His famous principle, "Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, Tut Wuri Handayani," describes the role of parents in various positions to educate children: providing example, and encouragement. According to Ki Hajar Dewantara, education in the family must also foster children's independence and responsibility, as well as giving them the freedom to explore their interests and talents. Meanwhile, Driyarkara emphasized that the family is the first place of a persons's presence as a human being, and the family is the first step in the process of his journey towards becoming a full human being. Overall, Driyarkara and Ki Hajar Dewantara's ideas about education in the family are related each other. Both agree that effective education starts from the family with an active and loving role of parents. While Driyarkara places more emphasis on holistic education and love, Ki Hajar Dewantara focuses on independence, freedom and the role of parents in supporting children from various educational positions. This writing uses a library research method sourced from both books and journals regarding the concept of family education according to Driyarkara and Ki Hadjar Dewantara. Through library sources, the author reads, adapts, summarizes and reports back ideas related to this article. Library study is also called text study. Using this method is very important because it is able to understand deeply and comprehensively the concept of family education according to Driyarkara and Ki Hajar Dewantara.AbstrakArtikel ini menampilkan pemikiran serta gagasan Driyarkara dan Ki Hajar Dewantara tentang pendidikan di dalam keluarga. Ki Hajar Dewantara, mengemukakan konsep Tri Pusat Pendidikan, yang menyatakan bahwa pendidikan terjadi di keluarga, sekolah, dan masyarakat, dengan keluarga sebagai lingkungan pendidikan pertama dan utama. Prinsipnya yang terkenal, "Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, Tut Wuri Handayani," menggambarkan peran orang tua dalam berbagai posisi untuk mendidik anak: memberi teladan, semangat, dan dorongan. Pendidikan dalam keluarga menurut Ki Hajar Dewantara juga harus menumbuhkan kemandirian dan tanggung jawab anak, serta memberikan kebebasan untuk mengeksplorasi minat dan bakat mereka. Secara keseluruhan, pandangan Driyarkara dan Ki Hajar Dewantara mengenai pendidikan dalam keluarga saling melengkapi. Keduanya sepakat bahwa pendidikan yang efektif dimulai dari keluarga dengan peran orang tua yang aktif dan penuh kasih sayang. Sementara Driyarkara lebih menekankan pada pendidikan holistik dan cinta kasih, Ki Hajar Dewantara fokus pada kemandirian, kebebasan, dan peran orang tua dalam mendukung anak dari berbagai posisi pendidikan.